2017
DOI: 10.3151/jact.15.595
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among the Permeation Rate of Water into Concrete, the Mix Design, Curing, and the Degree of Drying

Abstract: Water permeation into concrete causes various types of deterioration in concrete structures such as rebar corrosion, frost damage, ASR, etc.; however, the evaluation of the water permeation rate is difficult. This paper proposes a simple equation to evaluate the water permeation rate into concrete, based on basic information such as the mix design, curing condition, and degree of drying. Concrete specimens are cast, cut into slices of different thicknesses, and the time taken for water penetration is measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The comparison between A calculated using Eq. (13) and that calculated from the data in the literature (Koshikawa and Ogihara 1991;Sakai and Kishi 2016;Sakai et al 2017;Suzuki and Ueda 2015;Tsuchiya et al 2008;Ueda and Suzuki 2016a;Zhang et al 2011) is shown in Fig. 4.…”
Section: Design Water Penetration Rate Coefficientmentioning
confidence: 70%
See 4 more Smart Citations
“…The comparison between A calculated using Eq. (13) and that calculated from the data in the literature (Koshikawa and Ogihara 1991;Sakai and Kishi 2016;Sakai et al 2017;Suzuki and Ueda 2015;Tsuchiya et al 2008;Ueda and Suzuki 2016a;Zhang et al 2011) is shown in Fig. 4.…”
Section: Design Water Penetration Rate Coefficientmentioning
confidence: 70%
“…4. The test conditions used in these studies are summarized in Sakai et al (2017). Thus far, the number of studies in literature that have reported the rate of increase of the water penetration depth with time is limited; to the best of the authors' knowledge, the data reported here constitute all the literature that the authors could find.…”
Section: Design Water Penetration Rate Coefficientmentioning
confidence: 98%
See 3 more Smart Citations